Quantum mechanics - Merzbacher, Eugen (New Delhi: John Wiley, 2004)
This computer-based laboratory manual contains experiments in mechanics, thermodynamics, E&M, and optics using hardware and software designed to enhance readers' understanding of calculus-based physics concepts. The manual makes use of an active learning cycle, including concept overviews, hypothesis-testing, prediction-making, and investigations.
Appendix 630-641p.; Include bibliographical references 642-646p.; Index 647-656p.
Keywords: Linear harmonic oscillater; Quantum mechanics; Vector space; General Science